Tradition, Folklore, Modernity. Upper Sorbian and Kashubian Culture Through the Eyes of Its Young Representatives - Dołowy-Rybińska, Nicole (Poznańskie Studia Slawistyczne, 2015)
The article is based on a participatory observation and semi-structured interviews conducted in 2012 and 2013 with young (aged 16–25) Upper Sorbs and Kashubs. They were asked about their perception of the Upper Sorbian/Kashubian culture, its relation with the past, tradition and folklore, reception of the dominant image of their culture and the existence of a modern dimension of the Upper Sorbian/Kashubian culture. An analysis of the young peoples’ statements and anthropological research shows that a relation with tradition is still important for minority culture participants although it depends on the way this culture is lived. In the case of the Upper Sorbs some of the traditions, related to the Catholic culture, are alive and constitute an important part of community life. They are perceived as the ‘authentic’ ones. The Kashubian culture, however, has been strongly folklorized and young people do not identify with the folkloric representations and image of this culture, which is treated as an artificial phenomenon. Young people of both cultures want their culture to be modern yet, at the same time, have a connection with the past.